2017
DOI: 10.1177/0890117117698088
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education and Sport: Does Participation Relate to Physical Activity Patterns, Observed Fitness, and Personal Attitudes and Beliefs?

Abstract: iii I hereby declare that all information in this document has been obtained and presented in accordance with academic rules and ethical conduct. I also declare that, as required by these rules and conduct, I have fully cited and referenced all material and results that are not original to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
2
18
1
3
Order By: Relevance
“…The prevalence of attending two or more PE classes observed in the present study was low (41.9%), lower compared with other studies in United States (81.6%) 17 and Canada (76.8%) 18 , as well as studies in Santa Catarina state (48.1%) 5 , Paraná state (78.9%) 19 and São Paulo city (49.5) 6 . However, it was higher than studies that were performed with high school students in Pernambuco state (35.15 4 to 37.6%) 20 .…”
Section: Discussioncontrasting
confidence: 84%
“…The prevalence of attending two or more PE classes observed in the present study was low (41.9%), lower compared with other studies in United States (81.6%) 17 and Canada (76.8%) 18 , as well as studies in Santa Catarina state (48.1%) 5 , Paraná state (78.9%) 19 and São Paulo city (49.5) 6 . However, it was higher than studies that were performed with high school students in Pernambuco state (35.15 4 to 37.6%) 20 .…”
Section: Discussioncontrasting
confidence: 84%
“…In one school, those minutes were distributed among three classes of 50 min, while in the other school, they were divided into two classes, of 50 and 100 min. Several investigations have proposed that daily PE provides better opportunities for enhancing PA and fitness [34][35][36][37]. Also, the content of PE is of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of PA and sedentarism have been associated with the onset of different pathologies and health problems [6,7]. Numerous studies have demonstrated that doing regular PA is beneficial for body composition [8][9][10], bone health [11,12], psychological health and stress [13,14], and cardiorespiratory capacity, among others [15][16][17][18]. The prevalence of these illnesses is still increasing, leading to greater morbidity and mortality, and the consequent urgent need to implement effective PA programs to reduce the sedentary behavior of the population [19].…”
Section: Introductionmentioning
confidence: 99%